GALE variants associated with syndromic manifestations, macrothrombocytopenia, bleeding, and platelet dysfunction. (31st December 2023) - Marín-Quílez, Ana; Di Buduo, Christian A.; Benito, Rocío; Balduini, Alessandra; Rivera, José; Bastida, Jose Maria
Abstract: GALE gene encodes the uridine diphosphate [UDP]-galactose-4-epimerase, which catalyzes the bidirectional interconversion of UDP-glucose to UDP-galactose, and UDP-N-acetyl-glucosamine to UDP-N-acetyl-galactosamine. In that way, GALE balances, through reversible epimerization, the pool of four sugars that are essential during the biosynthesis of glycoproteins and glycolipids. GALE -related disorder presents an autosomal recessive inheritance pattern, and it is commonly associated with galactosemia. Peripheral galactosemia generally associates with non-generalized forms or even asymptomatic presentations, while classical galactosemia may be related to complications such as learning difficulties, developmental delay, cardiac failure, or dysmorphic features. Recently, GALE variants have been related to severe thrombocytopenia, pancytopenia, and in one patient, to myelodysplastic syndrome. Plain Language Summary: What is the context? GALE gene encodes for the UDP-Galactose 4-Epimerase, an enzyme involved in the Leloir pathway of galactose catabolism and protein glycosylation. Homozygous or compound heterozygous GALE variants associate with the disorder known as galactosemia type III. Three types of galactosemia can be distinguished: the peripheral, the intermediate, and the generalized form, which associate with different clinical symptoms and GALE genetic variants. Peripheral form is considered benign, while the intermediate and the generalized form is associated with severe and syndromic manifestations, including learning difficulties, delayed growth, sensorineural hearing loss, and early-onset cataracts, among others. What is new? In the last few years, GALE variants have been linked to hematological manifestations, such as anemia, febrile neutropenia, and severe thrombocytopenia. To date, the only GALE variants described in patients presenting hematological disorders are GALE p.Arg51Trp, p.Lys78ValfsX32, p.Val128Met, p.Thr150Met, p.Leu223Pro, and p.Gly237Asp. The thrombocytopenia observed in GALE patients is associated with reduced GPIbα and β1 integrin glycosylation and externalization to the megakaryocyte and platelet surface, disrupting the actin cytoskeleton remodeling. What is the impact? GALE is an essential protein for the correct megakaryocyte and platelet glycosylation.